Expression of the helix-loop-helix protein ID1 in keratinocytes is upregulated by loss of cell-matrix contact - Schäfer, Birgit; Koch, Judith; Wirzbach, Alexander; Kramer, Michael D. (Experimental cell research, 2001)
To analyze the inhibitor of DNA-binding type 1 (ID1) in the human epidermis and in cultured keratinocytes we generated and characterized ID1-specific monoclonal antibodies. Immunohistological studies on human skin biopsies revealed that ID1 is not detectable in normal human epidermis but in lesional epidermis of bullous pemphigoid. In the latter case we found ID1 in the cytoplasm of basal and proximal suprabasal keratinocytes. Cultured normal human epidermal keratinocytes displayed ID1 in the cytoplasm; upon differentiation into a multilayered keratinocyte sheet, ID1 was no longer detectable. It was reexpressed after dispase-mediated detachment of the keratinocyte cultures from the growth substratum. In this case ID1 was localized to the cytoplasm and the nucleus. Our data indicate that after epidermal injury-in our case loss of cell-matrix contact-ID1 is upregulated in affected keratinocytes. In view of the ID1 function in other cell types, we speculate that ID1 facilitates the transition from the resting to the migrating and proliferating keratinocyte required for efficient repair of epidermal lesions by reepithelialization. Taken together we suggest that ID1 is an important player in epidermal (patho-)physiology.
Gesehen am 22.02.2021